Insights into the Chemical Durability and Structure of ZnO-Incorporated Sodium Borosilicate Glasses from Solid-State NMR - Illath, Kavya; Ananthanarayanan, Arvind; Banerjee, D.; Mishra, R. K.; Kumar, Ravi; Bhattacharya, D.; Kumar, Sanjay; Manohar, S.; Ajithkumar, T. G. (Journal of Physical Chemistry B, 2025)
ZnO-incorporated NBS glasses have been studied for their application as a matrix for nuclear waste immobilization. However, structural factors affecting chemical durability have not been established. In this study, the structural changes in NBSZn glasses across various Na2O/(B2O3 + ZnO) ratios are explored using multinuclear MAS, MQMAS NMR, and EXAFS techniques. The Na MAS and MQMAS studies reveal remarkable changes in the Na environment after ZnO incorporation, which leads to an increase in chemical durability. Based on the results from NMR and EXAFS, we rationalized the structure of this glass in terms of the modified random network (MRN) model. The glass network comprises a highly polymerized region and alkali percolation channels bordered by nonbridging oxygens from the depolymerized regions. The constriction of these percolation channels increases the chemical durability of the glass. Our findings will help in the advancement of Zn-containing NBS glasses as a promising matrix for nuclear waste immobilization.

Fly-ash-based geopolymers: leachability and solid-state NMR investigations - Nadol, Athulya; Ajithkumar, T. G.; Singla, Rashmi; Alex, T. C.; Kumar, Sanjay; Bhatt, Himal; Deo, M. N.; Sen, Debasis; Ambashta, R. D.; Bajpai, R. K.; Shivakumar, Y. C.; Manohar, S. (Bulletin of Materials Science, 2026)
This study aims to explore how leaching impacts the microstructure of a selected fly ash-derived geopolymer and evaluate its potential for near-surface disposal of radioactive waste. The uniqueness of this geopolymer formulation is its ability to form an aluminosilicate network that remains resistant to structural changes upon contact with water. The leach index of base elements such as Ca, Al, Na and Si was between 11 and 13, suggesting that the formulation is superior to Portland cement or conventional hydraulic cement. Solid-state NMR reveals that the water-interacted specimen has no contamination of the zeolite phase and all the Na is incorporated into the aluminosilicate geopolymer gel network, which also confirms that the glassy network of the geopolymer is responsible for imparting low leachability of base elements from its structure, and there is no labile sodium available for exchange as in zeolites.
Keywords: aluminosilicate network; Fly ash; Geopolymers; leaching; Solid-state NMR